2017
DOI: 10.3892/ijmm.2017.3211
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hypoglycemic and hepatocyte-protective effects of hyperoside from Zanthoxylum bungeanum leaves in mice with high-carbohydrate/high-fat diet and alloxan-induced diabetes

Abstract: The development of diabetes mellitus (DM) is accompanied by hyperglycemia-induced oxidative stress. Hyperoside is a major bioactive component in Zanthoxylum bungeanum leaves (HZL) and is a natural antioxidant. However, the effects of HZL on DM and its mechanisms of action remain undefined. The present study evaluated the anti-hypoglycemic and hepatocyte-protective effects of HZL in mice with diabetes induced by a high-carbohydrate/high-fat diet (HFD) and alloxan. We also aimed to eludicate the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 56 publications
3
27
0
Order By: Relevance
“…Hyperoside, also known as quercetin-3-O-b-D-galactopyranoside, is found in the fruit or whole plant of Hypericaceae, Rosaceae, Campanulaceae and Celastraceae plants, and belongs to the group of flavonol glycosides, with hepatoprotective, anticancer, bacteriostatic and memory-improving properties [7][8][9]. In addition, hyperoside can protect against myocardial I/R injury by inhibiting endoplasmic reticulum stress and activating the Nrf2 signalling pathway [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperoside, also known as quercetin-3-O-b-D-galactopyranoside, is found in the fruit or whole plant of Hypericaceae, Rosaceae, Campanulaceae and Celastraceae plants, and belongs to the group of flavonol glycosides, with hepatoprotective, anticancer, bacteriostatic and memory-improving properties [7][8][9]. In addition, hyperoside can protect against myocardial I/R injury by inhibiting endoplasmic reticulum stress and activating the Nrf2 signalling pathway [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, according to the results of the structure–activity relationship of nine flavonoids from Z. bungeanum leaves (Zhang, Wang, Yang, Zhou, & Zhang, ) and the correlation between the chromatographic fingerprint and antioxidant activity of the 22 subsequent fractions of Z. bungeanum leaves ethanol extracts (Zhang, Luo, Wang, He, & Li, ; Zhang, Luo, & Wang, ), it was found that quercitrin, hyperoside, rutin, and afzelin were the dominant flavonoids, which played a major role in antioxidant and antimicrobial activity. Furthermore, hyperoside from Z. bungeanum leaves also exerts many bioactivities, such as antiproliferative effects against SW620 (Zhang, Dong, Zhang, & Zhang, ) and antihyperglycemic and hepatocyte‐protective effects (Zhang, Wang, Dong, Yu, & Zhang, ). Therefore, in view of these benefits, it is necessary to establish a simple, low‐cost and efficient purification method for the four flavonoids from Z. bungeanum leaves.…”
Section: Introductionmentioning
confidence: 99%
“…This cell line is a well-defined in vitro model for studying the adipogenesis mechanism. In the literature, both in vivo and in vitro anti-obesity activity of hyperoside has not been studied sufficiently (13,14). In vitro models allow the investigation of the effects of the molecule on both preadipocytes and adipocytes at the molecular level.…”
Section: Discussionmentioning
confidence: 99%